2000
DOI: 10.1080/10408690091189275
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene in Tomatoes: Chemical and Physical Properties Affected by Food Processing

Abstract: Lycopene is the pigment principally responsible for the characteristic deep-red color of ripe tomato fruits and tomato products. It has attracted attention due to its biological and physicochemical properties, especially related to its effects as a natural antioxidant. Although it has no provitamin A activity, lycopene does exhibit a physical quenching rate constant with singlet oxygen almost twice as high as that of beta-carotene. This makes its presence in the diet of considerable interest. Increasing clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
509
1
29

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 731 publications
(563 citation statements)
references
References 78 publications
(113 reference statements)
24
509
1
29
Order By: Relevance
“…Our hypothesis was that the lycopene from the high lycopene carrot was bioavailable, however, not as bioavailable as that from tomato paste. This hypothesis is based on studies that have indicated lycopene from processed tomato products is more bioavailable than raw tomatoes (Porrini et al, 1998;Bohm & Bitsch, 1999;Shi & Le Mague, 2000). In addition, these experiments allow us to examine the effect of carrot fiber on lycopene absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our hypothesis was that the lycopene from the high lycopene carrot was bioavailable, however, not as bioavailable as that from tomato paste. This hypothesis is based on studies that have indicated lycopene from processed tomato products is more bioavailable than raw tomatoes (Porrini et al, 1998;Bohm & Bitsch, 1999;Shi & Le Mague, 2000). In addition, these experiments allow us to examine the effect of carrot fiber on lycopene absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The primary dietary source of lycopene is the tomato, with 85% coming from tomato products in the US (Arab & Steck, 2000). Lycopene, while having no provitamin A activity, is a potent antioxidant with twice the activity of b-carotene for quenching singlet oxygen and 10 times the in vitro antioxidant activity of a-tocopherol (DiMascio et al, 1989;Shi & Le Mague, 2000). Epidemiological evidence suggests an inverse association between dietary lycopene and the development of certain types of cancer (Agarwal & Rao, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lycopene content of tomato products is highly variable, being affected by factors such as variety (Hart & Scott, 1995;Abushita et al, 2000), ripeness (Fraser et al, 1994), climate and geographical site of production (Scalfi et al, 2000) and processing (Tonucci et al, 1995;Shi & Le Maguer, 2000;Re et al, 2002). For Body mass index (mean, SE) 412 24.8(0.6) 24.2(0.9) 24.8(0.9) 24.5 (0.8) 26.2 (0.9) 26.2 (0.9) 23.3 (1.0) 25.8 (1.2) 0.4 a TCP=tomato-containing products.…”
Section: Discussionmentioning
confidence: 99%
“…fine chopping) that help to break down the plant matrix (e.g. chloroplasts and chromoplasts) to which lycopene was firmly bound previously (Stahl & Sies, 1992;Shi & Le Maguer, 2000).…”
Section: Introductionmentioning
confidence: 99%